Titanium modified hydrofining catalyst as well as preparation method and application thereof
By using water as solvent and alumina as support in the hydrorefining catalyst, titanium modified catalyst was prepared, which solved the problems of uneven dispersion and high cost of Ti species, achieved high activity and stability improvement of the catalyst, and simplified the The preparation process and reduces wastewater discharge.
Patent Information
- Application Number
- CN202310804674.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-30
AI Technical Summary
During the preparation of traditional Ti modified Co(Ni)Mo(W) catalysts, there are problems of uneven dispersion, agglomeration and poor stability of Ti species, and the use of organic alcohols or acidic water solvents leads to high wastewater discharge and cost.
Using water as a solvent, titanium modified hydrorefining catalyst is prepared through aging and calcining treatment, alumina is used as a support, and titanium-containing compounds are used as the second co-active metal component to promote uniform dispersion of Ti species and strengthen the active metal and Ti. Electron interaction modulates the interaction force between active metal and carrier.
The catalyst's hydrodesulfurization and hydrodenitrogenation reaction activities are improved, production costs are reduced, the preparation process is simplified, the use of organic alcohols or acidic water is avoided, and the stability and activity of the catalyst is improved.
Smart Images

Figure CN119236961A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of petrochemical industry, and in particular to a titanium-modified hydrorefining catalyst, a preparation method thereof, and applications thereof. Background Art
[0002] Oil combustion produces SO x and NO x To reduce the production of pollutants such as sulfur and nitrogen, it is necessary to limit the sulfur and nitrogen content of refined oil products, promote oil quality upgrades, and produce cleaner oil products. However, after a century of development, the quality of crude oil is continuously declining. How to effectively balance the contradiction between the high sulfur content and poor quality of crude oil and the strong demand for clean oil products is a core issue facing the entire oil refining industry, especially the oil refining process that primarily produces fuel oil.
[0003] Hydrodesulfurization, a crucial process in oil processing, is a key technology for producing clean oils, and its core lies in the development of hydrogenation catalysts. After years of development, the commonly used hydrodesulfurization catalysts in industry have evolved into traditional supported Co(Ni)Mo(W) sulfide catalyst systems, with Mo and / or W as the primary active metal components and Co and / or Ni as co-active metal components. To address the conflict between declining crude oil quality and the need to upgrade to cleaner oils, the development of supported Co(Ni)Mo(W) catalysts with higher activity and stability is a key goal for ensuring the future production of clean oils.
[0004] Currently, the development of supported Co(Ni)Mo(W) catalysts focuses on three main areas: First, by introducing different additives to modulate the interaction between the active metal and the support or the electronic state of the active metal, the dispersion and reducibility of the active metal are improved, and the microstructure of the sulfided active phase is controlled, thereby enhancing the hydrodesulfurization activity of the catalyst. Second, by introducing acidic sites into the system, the adsorption capacity of active species on the catalyst surface is modulated or the formation of active sites (sulfur vacancies) is promoted, thereby achieving the purpose of improving catalyst activity and modulating catalyst selectivity. Third, constructing a support with a high specific surface area for loading the active metal, by improving the dispersion of the active metal, exposing more active centers, and improving the hydrodesulfurization activity of the catalyst.
[0005] Of the three methods mentioned above, the introduction of additives into traditional supported Co(Ni)Mo(W) catalysts to enhance their activity is relatively simple and low-cost, facilitating subsequent catalyst industrialization. Due to the limited availability of Ti metal salts and their tendency to hydrolyze during use, early Ti-modified Co(Ni)Mo(W) catalysts often employed prefabricated solid TiO2 or TiO(OH) as the titanium source, mechanically mixing the Ti source with the support through kneading. This inevitably resulted in uneven Ti dispersion and poor thermal stability of agglomerated Ti species, resulting in limited activity enhancement and poor stability of Ti-modified Co(Ni)Mo(W) catalysts. To address these issues, literature reports have reported the use of organic titanium salts or sulfates as the titanium source, dissolving them in alcohols or acidic water. A Ti-modified composite support was prepared through a series of steps, including precipitation, filtration, washing, drying, and calcination. The active metal was then loaded onto the support through impregnation, followed by secondary drying and calcination to produce the Ti-modified Co(Ni)Mo(W) catalyst. However, the existing preparation process requires the use of alcohols or acidic water as solvents, which will significantly increase the wastewater discharge during the catalyst preparation process. At the same time, the preparation process of such catalysts is long and the cost is high. Summary of the Invention
[0006] The purpose of the present disclosure is to provide a titanium-modified hydrorefining catalyst and a preparation method and application thereof, which can be easily prepared and has high catalytic activity.
[0007] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a titanium-modified hydrotreating catalyst. Based on the total weight of the titanium-modified hydrotreating catalyst, the titanium-modified hydrotreating catalyst includes 50 to 80 weight% of a carrier, 10 to 40 weight% of a main active metal component, 1 to 15 weight% of a first auxiliary active metal component and 1 to 30 weight% of a second auxiliary active metal component; the main active metal component is selected from one or more of the metal elements of Group VIB, the first auxiliary active metal component is selected from one or more of the metal elements of Group VIII, and the second auxiliary active metal component includes titanium; the carrier includes alumina.
[0008] Optionally, the main active metal component includes oxides of one or both metal elements selected from Mo and W; the first auxiliary active metal component includes oxides of one or both metal elements selected from Ni and Co; and the second auxiliary active metal component includes titanium oxide.
[0009] Optionally, the total acid content of the titanium modified hydrorefining catalyst measured by pyridine infrared at 150°C is 140 to 190 μmol / g, Acid center content is less than 10 μmol / g;
[0010] Optionally, the BET specific surface area of the titanium modified hydrorefining catalyst is 150 to 250 m 2 / g, with a total pore volume greater than 0.4 cm 3 / g.
[0011] Optionally, the titanium modified hydrotreating catalyst comprises Ti 3+ species;
[0012] Preferably, the Ti 2p 3 / 2 In the XPS spectrum of the orbital, the peak area of all titanium elements is used as the basis. 3+ The peak area proportion of the species is 3 to 40%, preferably 8 to 20%.
[0013] A second aspect of the present disclosure provides a method for preparing a titanium-modified hydrorefining catalyst, comprising the following steps:
[0014] S1. Mixing a main active metal component precursor, a first co-active metal component precursor, a second co-active metal component precursor, water, and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; wherein the metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the first co-active metal component precursor is selected from one or more metal elements of Group VIII, and the second co-active metal component precursor includes a titanium-containing compound;
[0015] S2. Mixing the catalyst intermediate with an auxiliary agent, and performing molding and calcining treatments.
[0016] Optionally, the main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid;
[0017] The first co-active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate;
[0018] The second auxiliary active metal component precursor is selected from one or more of titanium tetrachloride, methyl titanate, tetraethyl titanate, titanium n-propoxide, isopropyl titanate, tetrabutyl titanate, titanium tert-butoxide and titanium isooctoxide; preferably, one or more of tetraethyl titanate, isopropyl titanate and tetrabutyl titanate;
[0019] The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
[0020] Optionally, in step S1, the aging treatment conditions include: natural aging at 0-50°C for 12-24h;
[0021] Optionally, the method further comprises: drying the product obtained by the aging treatment at 80-160° C. for 4-12 hours.
[0022] Optionally, in step S2, the calcination treatment conditions include: calcination at 300-700° C. for 3-10 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor;
[0023] Optionally, before the calcination process, the product obtained by the molding process is dried at 80-160° C. for 4-12 hours.
[0024] A third aspect of the present disclosure provides a titanium-modified hydrorefining catalyst prepared according to the method described in the second aspect of the present disclosure.
[0025] The fourth aspect of the present disclosure provides the use of the titanium-modified hydrorefining catalyst described in the first and third aspects of the present disclosure in a feedstock oil hydrorefining reaction.
[0026] Optionally, the following steps are included:
[0027] Under hydrogen conditions, the crude oil is brought into contact with the titanium-modified hydrorefining catalyst to carry out a hydrorefining reaction;
[0028] Optionally, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; raw oil mass space velocity of 0.1-6h -1 ;
[0029] Optionally, the feedstock oil is selected from gasoline and / or diesel fractions;
[0030] Preferably, the method further comprises: performing a sulfurization treatment on the titanium modified hydrorefining catalyst before performing the hydrorefining reaction.
[0031] Through the above technical solution, the present disclosure provides a titanium-modified hydrorefining catalyst, its preparation method and application. The titanium-modified hydrorefining catalyst uses a Group VIB metal element as the main active metal component, a Group VIII metal element as the first auxiliary active metal component, and titanium as the second auxiliary active metal component. The preparation method is simple and effective, and can effectively avoid the use of organic alcohols or acidic water in the traditional preparation process, thereby reducing production costs. At the same time, the titanium-modified hydrorefining catalyst can promote the uniform dispersion of Ti species in the catalyst, strengthen the electronic interaction between the active metal and the Ti species, modulate the interaction between the active metal and the carrier, improve the dispersibility of the active metal and the microstructure of the active species, and obtain a catalyst with a "surface microsphere structure", which significantly improves the catalyst's hydrodesulfurization and hydrodenitrogenation reaction activity.
[0032] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following detailed description, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0034] Figure 1 is a scanning electron microscope photograph of the titanium-modified hydrorefining catalyst prepared in Example 1;
[0035] Figure 2 The Ti 2p of the titanium modified hydrorefining catalyst prepared in Example 1 3 / 2 XPS spectrum. DETAILED DESCRIPTION
[0036] The following describes the specific embodiments of the present disclosure in detail. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure and are not intended to limit the present disclosure.
[0037] In a first aspect, the present disclosure provides a titanium-modified hydrotreating catalyst. Based on the total weight of the titanium-modified hydrotreating catalyst, the titanium-modified hydrotreating catalyst comprises 50 to 80 weight percent of a carrier, 10 to 40 weight percent of a main active metal component, 1 to 15 weight percent of a first auxiliary active metal component, and 1 to 30 weight percent of a second auxiliary active metal component; the main active metal component is selected from one or more metal elements of Group VIB, the first auxiliary active metal component is selected from one or more metal elements of Group VIII, and the second auxiliary active metal component includes titanium; the carrier includes alumina.
[0038] The present disclosure provides a titanium-modified hydrorefining catalyst, wherein the titanium-modified hydrorefining catalyst uses a Group VIB metal element as the main active metal component, a Group VIII metal element as the first auxiliary active metal component, and titanium as the second auxiliary active metal component. The preparation method is simple and effective, effectively avoiding the use of organic alcohols or acidic water in the traditional preparation process, thereby reducing production costs. At the same time, the titanium-modified hydrorefining catalyst can promote the uniform dispersion of Ti species in the catalyst, strengthen the electronic interaction between the active metal and the Ti species, modulate the interaction between the active metal and the carrier, improve the dispersibility of the active metal and the microstructure of the active species, and obtain a catalyst with a "surface microspherical structure", thereby significantly improving the catalyst's hydrodesulfurization and hydrodenitrogenation reaction activity.
[0039] In the present disclosure, the contents of the main active metal component, the first co-active metal component and the second co-active metal component in the catalyst are calculated in the form of metal oxides.
[0040] In a preferred embodiment, the titanium-modified hydrorefining catalyst comprises 50-70 wt% of a carrier, 20-30 wt% of a main active metal component, 4-10 wt% of a first auxiliary active metal component and 5-15 wt% of a second auxiliary active metal component.
[0041] In one embodiment, the main active metal component includes an oxide of one or both metal elements selected from Mo and W; the first auxiliary active metal component includes an oxide of one or both metal elements selected from Ni and Co; and the second auxiliary active metal component includes titanium oxide.
[0042] In a preferred embodiment, the total acid content of the titanium modified hydrorefining catalyst measured by pyridine infrared at 150°C is 140 to 190 μmol / g, preferably 160 to 185 μmol / g. Acid center content is less than 10 μmol / g;
[0043] Optionally, the BET specific surface area of the titanium modified hydrorefining catalyst is 150 to 250 m 2 / g, with a total pore volume greater than 0.4 cm 3 / g.
[0044] In one embodiment, the titanium modified hydrotreating catalyst comprises Ti 3+ species.
[0045] In a preferred embodiment, the Ti 2p 3 / 2 In the XPS spectrum of the orbital, the peak area of all titanium elements is used as the basis. 3+The peak area of the species accounts for 3 to 40%, preferably 8 to 20%. 3 / 2 The peak area at 456.9 eV in the XPS spectrum of the orbital indicates that Ti 3+ Species content, the peak area at 458.7eV represents Ti 4+ Species content, as Ti 3+ Species and Ti 4+ The total area of the species peak represents the content of all titanium elements, Ti 3+ The content of species is attributed to Ti 3+ The peak area of species attributed to Ti 3+ Species and Ti 4+ The ratio of the sum of the peak areas of the species.
[0046] A second aspect of the present disclosure provides a method for preparing a titanium-modified hydrorefining catalyst, comprising the following steps:
[0047] S1. Mixing a main active metal component precursor, a first co-active metal component precursor, a second co-active metal component precursor, water, and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; wherein the metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the first co-active metal component precursor is selected from one or more metal elements of Group VIII, and the second co-active metal component precursor includes a hydrolyzable titanium-containing compound;
[0048] S2. Mixing the catalyst intermediate with an auxiliary agent, and performing molding and calcining treatments.
[0049] In the method for preparing a titanium-modified hydrorefining catalyst provided by the present disclosure, water is used as a solvent, which can effectively avoid the use of organic alcohols or acidic water in the traditional preparation process and reduce production costs; and the present disclosure uses a hydrolyzable titanium-containing compound as a second auxiliary active metal component precursor together with a main active metal component precursor, a first auxiliary active metal component precursor and an alumina precursor to prepare a titanium-modified hydrorefining catalyst. The titanium-containing compound precursor can be hydrolyzed in situ, which is conducive to the uniform dispersion of Ti species in the catalyst, strengthening the electronic interaction between the active metal and the Ti species, regulating the interaction force between the active metal and the carrier, improving the dispersibility of the active metal and the microstructure of the active species, and significantly improving the hydrodesulfurization and hydrodenitrogenation reaction activity of the catalyst.
[0050] In the present disclosure, the addition amount and addition ratio of each raw material can be adjusted according to the target component composition of the titanium-modified hydrorefining catalyst.
[0051] In one specific embodiment, in step S1, the weight ratio of the main active metal component precursor: the first co-active metal component precursor: the second co-active metal component precursor: water: the alumina precursor is 0.2-2: 0.1-1.5: 0.1-2.5: 1-4: 1. Catalyst preparation according to the weight ratios of the raw materials specified in this embodiment can produce a titanium-modified hydrorefining catalyst with improved catalytic performance.
[0052] In a specific embodiment, the main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid;
[0053] The first co-active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate;
[0054] The alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
[0055] In a preferred embodiment, the second auxiliary active metal component precursor is selected from one or more of titanium tetrachloride, methyl titanate, tetraethyl titanate, titanium n-propoxide, isopropyl titanate, tetrabutyl titanate, titanium tert-butoxide and titanium isooctoxide; preferably, it is selected from one or more of tetraethyl titanate, isopropyl titanate and tetrabutyl titanate.
[0056] In one embodiment, a solution of the main active metal component precursor and the first co-active metal component precursor can be prepared with water. This solution, along with the second co-active metal component precursor, can then be dropwise added to the alumina precursor. The solution is then stirred and mixed, and then aged. Conventional equipment and conditions can be used for stirring and mixing to ensure uniform mixing of the raw materials.
[0057] In one embodiment, in step S1, the aging treatment conditions include: natural aging at 0-50°C for 12-24 hours; preferably, natural aging at 5-30°C for 12-20 hours.
[0058] In one embodiment, the method further comprises: drying the product obtained by the aging treatment at 80-160° C. for 4-12 hours.
[0059] In a specific embodiment, in step S2, the molding process includes extrusion molding and reverse molding, preferably extrusion molding. The specific process and apparatus of extrusion molding are well known to those skilled in the art.
[0060] In one embodiment, the auxiliary agent includes an extrusion aid and a binder;
[0061] The extrusion aid is selected from one or more of starch, sesbania powder, polyethylene glycol and methyl cellulose; preferably, the amount of the extrusion aid added is 1 to 10% by weight, preferably 3 to 8% by weight, based on the total weight of the components;
[0062] The binder is selected from one or more of nitric acid, citric acid, tartaric acid, oxalic acid and oxalic acid; preferably, the addition amount of the binder is 1 to 10 weight %, preferably 3 to 8 weight %, based on the total weight of all components.
[0063] The reagents used in the present disclosure can be purchased through conventional channels or prepared by known methods.
[0064] In one embodiment, the catalyst product obtained by the shaping process may have a strip shape, a clover shape, a granular shape, or a toothed ball shape.
[0065] In one embodiment, in step S2, the calcination treatment conditions include: calcination at 300-700°C for 3-10 hours, preferably, calcination at 400-600°C for 4-7 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor;
[0066] Optionally, before the calcination process, the product obtained by the molding process is dried at 80-160° C. for 4-12 hours.
[0067] During the preparation of the catalyst, each step can be carried out using conventional equipment in the art.
[0068] A third aspect of the present disclosure provides a titanium-modified hydrorefining catalyst prepared according to the method described in the second aspect of the present disclosure.
[0069] The fourth aspect of the present disclosure provides use of the titanium-modified hydrorefining catalyst described in the first aspect or the third aspect in a feedstock oil hydrorefining reaction.
[0070] In one embodiment, the process comprises the following steps: contacting the crude oil with a titanium-modified hydrorefining catalyst under hydrogenation conditions to carry out a hydrorefining reaction.
[0071] In one embodiment, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; feed oil mass space velocity of 0.1-6h -1 ;
[0072] Optionally, the feedstock oil is selected from gasoline and / or diesel fractions.
[0073] In the present disclosure, the titanium-modified hydrotreating catalyst is subjected to a sulfurization treatment before the hydrotreating reaction is performed.
[0074] In a preferred embodiment, the temperature of the sulfurization treatment is 200-500°C, the pressure is 0.1-10 MPa, the time of the sulfurization treatment is 1-60 hours, and the liquid hourly space velocity is 0.1-20 hours. -1 , the hydrogen-to-oil volume ratio is 100-800.
[0075] The present disclosure is further described in detail below through examples. The raw materials used in the examples are all commercially available. The performance tests were performed using instruments commonly used in the field.
[0076] The methods for determining and calculating the total content of the oxides of the active component metals in the catalyst are well known in the art, specifically including XRF and ICP methods.
[0077] The test method for acid content includes pyridine infrared method.
[0078] The BET specific surface area of the sample was determined by nitrogen physical adsorption at low temperature.
[0079] Ti 2p was used to test the Ti content in the catalyst. 3 / 2 Test of XPS orbital spectrum.
[0080] Example 1
[0081] This embodiment provides a titanium-modified hydrorefining catalyst, and the specific preparation method includes the following steps:
[0082] (1) Take 3.14g of ammonium metatungstate and 1.95g of nickel nitrate and dissolve them in 24.77g of deionized water to prepare a mixed impregnation solution. Take another 4.34g of tetrabutyl titanate and 8.26g of pseudo-boehmite for later use. Add the mixed impregnation solution and tetrabutyl titanate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the first auxiliary active metal component precursor: the second auxiliary active metal component precursor: water: the alumina precursor is 0.38:0.24:0.53:3:1), stir vigorously for 2h to mix evenly, age naturally at 10°C for 12h, and then dry at 100°C for 8h to obtain a catalyst semi-finished product;
[0083] (2) The above catalyst powder was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated TC-1.
[0084] The TC-1 catalyst contained 27 wt% of tungsten oxide (main active metal component), 5 wt% of nickel oxide (first auxiliary active metal component), and 10.2 wt% of titanium oxide (second auxiliary active metal component) in it.
[0085] The scanning electron microscope image of TC-1 catalyst is shown in Figure 2. Figure 1 As shown by Figure 1 It can be seen that the catalyst surface has a microspherical structure.
[0086] Ti 2p of TC-1 catalyst 3 / 2 XPS spectra such as Figure 2 As shown by Figure 2 It can be seen that the Ti 2p 3 / 2 The XPS spectrum shows Ti 3+ Species and Ti 4+ The characteristic peaks of the species are calculated by peak area, among which Ti 3+ The peak area of the species is 260, Ti 4+ The peak area of the species is 1473, Ti 3+ Species peak area / (Ti 3+ Species peak area + Ti 4+ Species peak area) × 100% is 15%.
[0087] Comparative Example 1
[0088] This comparative example provides a titanium-free hydrogenation catalyst, the specific preparation method of which comprises the following steps:
[0089] (1) Dissolve 3.14 g of ammonium metatungstate and 1.95 g of nickel nitrate in 29.14 g of deionized water to prepare a mixed impregnation solution. Separately, take 9.71 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, stir vigorously for 2 h to mix evenly, age naturally at 10° C. for 12 h, and then dry at 100° C. for 8 h to obtain a catalyst semi-finished product.
[0090] (2) The above catalyst powder was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated D-1.
[0091] It was determined that the content of tungsten oxide in the D-1 catalyst was 27% by weight, the content of nickel oxide was 5% by weight, and the total content of nickel oxide and tungsten oxide was 32.0% by weight (all based on the total weight of the catalyst).
[0092] Example 2
[0093] This embodiment provides a titanium-modified hydrorefining catalyst, and the specific preparation method includes the following steps:
[0094] (1) Take 2.82g of ammonium molybdate and 2.72g of cobalt nitrate and dissolve them in 26.40g of deionized water to prepare a mixed impregnation solution. Take another 2.99g of isopropyl titanate and 8.80g of pseudo-boehmite for later use. Add the mixed impregnation solution and isopropyl titanate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the first auxiliary active metal component precursor: the second auxiliary active metal component precursor: water: the alumina precursor is 0.32:0.31:0.34:3:1), stir vigorously for 2h to mix evenly, age naturally at 20℃ for 16h, and then dry at 110℃ for 6h to obtain a catalyst semi-finished product;
[0095] (2) The above-mentioned semi-finished catalyst was uniformly mixed with 0.4 g of polyethylene glycol, 0.2 g of nitric acid, 0.3 g of citric acid, and an appropriate amount of deionized water, and extruded into catalyst bars with a diameter of 1.5 mm. The resulting catalyst bars were dried at 120°C for 7 h, calcined at 500°C in air for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated TC-2.
[0096] It was measured that the content of molybdenum oxide (main active metal component) in the TC-2 catalyst was 23 weight %, the content of cobalt oxide (first auxiliary active metal component) was 7 weight %, and the content of titanium oxide (second auxiliary active metal component) was 8.4 weight % (all based on the total weight of the catalyst).
[0097] Comparative Example 2
[0098] This comparative example provides a titanium-free hydrogenation catalyst, the specific preparation method of which comprises the following steps:
[0099] (1) Dissolve 2.82 g of ammonium molybdate and 2.72 g of cobalt nitrate in 30.00 g of deionized water to prepare a mixed impregnation solution. Separately, take 10.00 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, vigorously stir for 2 h to mix evenly, age naturally at 20° C. for 16 h, and then dry at 110° C. for 6 h to obtain a semi-finished catalyst.
[0100] (2) The above-mentioned semi-finished catalyst was uniformly mixed with 0.4 g of polyethylene glycol, 0.2 g of nitric acid, 0.3 g of citric acid, and an appropriate amount of deionized water, and extruded into catalyst bars with a diameter of 1.5 mm. The resulting catalyst bars were dried at 120°C for 7 h, calcined at 500°C in air for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated D-2.
[0101] The content of molybdenum oxide in the D-2 catalyst was measured to be 23% by weight, and the content of cobalt oxide was measured to be 7% by weight (both based on the total weight of the catalyst).
[0102] Example 3
[0103] This embodiment provides a titanium-modified hydrorefining catalyst, and the specific preparation method includes the following steps:
[0104] (1) Take 1.72g of ammonium molybdate, 1.63g of ammonium metatungstate and 2.72g of nickel nitrate and dissolve them in 22.29g of deionized water to prepare a mixed impregnation solution. Separately take 2.23g of tetraethyl titanate, 1.85g of titanium n-propoxide and 7.43g of pseudo-boehmite for later use. Add the mixed impregnation solution, tetraethyl titanate and titanium n-propoxide dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the first auxiliary active metal component precursor: the second auxiliary active metal component precursor: water: alumina precursor is 0.45:0.37:0.3:3:1), stir vigorously for 2h to mix evenly, age naturally at 8°C for 15h, and then dry at 120°C for 6h to obtain a catalyst semi-finished product;
[0105] (2) The above catalyst powder was uniformly mixed with 0.4 g of methyl cellulose, 0.2 g of nitric acid, 0.2 g of tartaric acid, and an appropriate amount of deionized water, and extruded into catalyst pellets with a diameter of 1.5 mm. The resulting catalyst pellets were dried at 80°C for 15 h, calcined at 450°C in air for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated TC-3.
[0106] It was measured that the TC-3 catalyst contained 14 weight % molybdenum oxide and 14 weight % tungsten oxide (the total content of the main active metal components was 28 weight %), 7 weight % nickel oxide (the first auxiliary active metal component), and 13.0 weight % titanium oxide (the second auxiliary active metal component) (all based on the total weight of the catalyst).
[0107] Comparative Example 3
[0108] This comparative example provides a titanium-free hydrogenation catalyst, the specific preparation method of which comprises the following steps:
[0109] (1) Dissolve 2.72 g of nickel nitrate, 1.72 g of ammonium molybdate, and 1.63 g of ammonium metatungstate in 27.86 g of deionized water to prepare a mixed impregnation solution. Separately, take 9.29 g of pseudo-boehmite for later use. Add the mixed impregnation solution dropwise onto the pseudo-boehmite, vigorously stir for 2 h, mix thoroughly, age naturally at 8°C for 15 h, and then dry at 120°C for 6 h to obtain a semi-finished catalyst.
[0110] (2) The above catalyst powder was uniformly mixed with 0.4 g of methyl cellulose, 0.2 g of nitric acid, 0.2 g of tartaric acid, and an appropriate amount of deionized water, and extruded into catalyst pellets with a diameter of 1.5 mm. The resulting catalyst pellets were dried at 80°C for 15 h, calcined at 450°C in air for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated D-3.
[0111] The D-3 catalyst was found to contain 14 wt% molybdenum oxide, 14 wt% tungsten oxide, and 7 wt% nickel oxide (based on the total weight of the catalyst).
[0112] Comparative Example 4
[0113] This comparative example refers to the preparation method of Example 1, and the difference from Example 1 is that the amount of raw materials added is changed, specifically including:
[0114] (1) Take 0.81g of ammonium metatungstate and 9.73g of nickel nitrate and dissolve them in 14.57g of deionized water to prepare a mixed impregnation solution. Take another 14.48g of tetrabutyl titanate and 4.86g of pseudo-boehmite for later use. Add the mixed impregnation solution and tetrabutyl titanate dropwise onto the pseudo-boehmite (wherein the weight ratio of the main active metal component precursor: the first auxiliary active metal component precursor: the second auxiliary active metal component precursor: water: the alumina precursor is 0.17:2:2.98:3:1), stir vigorously for 2h to mix evenly, age naturally at 10℃ for 12h, and then dry at 100℃ for 8h to obtain a catalyst semi-finished product;
[0115] (2) The above catalyst powder was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 80°C for 12 h, calcined at 500°C in a 15% O2 / N2 atmosphere for 4 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated D-4.
[0116] The D-4 catalyst contained 7 wt% tungsten oxide (main active metal component), 25 wt% nickel oxide (first auxiliary active metal component), and 50 wt% titanium oxide (second auxiliary active metal component) in it.
[0117] Example 4
[0118] This example refers to the preparation method of Example 1, and the difference from Example 1 is that the preparation conditions are changed, specifically including:
[0119] (1) Dissolve 3.14 g of ammonium metatungstate and 1.95 g of nickel nitrate in 24.77 g of deionized water to prepare a mixed impregnation solution. Separately, take 4.34 g of tetrabutyl titanate and 8.26 g of pseudo-boehmite. Add the mixed impregnation solution and tetrabutyl titanate dropwise onto the pseudo-boehmite, stir vigorously for 1 hour to mix evenly, age naturally at 60°C for 3 hours, and then dry at 80°C for 6 hours to obtain a catalyst semi-finished product.
[0120] (2) The above catalyst powder was uniformly mixed with 0.4 g of Tianqing powder, 0.2 g of nitric acid, 0.2 g of citric acid, and an appropriate amount of deionized water, and extruded into a clover-shaped catalyst with a diameter of 1.5 mm. The resulting clover-shaped catalyst was dried at 150°C for 4 h, calcined at 900°C in a 15% O2 / N2 atmosphere for 8 h, and naturally cooled to obtain a titanium-modified hydrorefining catalyst, designated TC-4.
[0121] The TC-4 catalyst contained 27 wt% of tungsten oxide (main active metal component), 5 wt% of nickel oxide (first auxiliary active metal component), and 10.2 wt% of titanium oxide (second auxiliary active metal component) in the catalyst.
[0122] Example 5
[0123] This example refers to the preparation method of Example 1, and the difference from Example 1 is that the amount of raw materials added is changed, specifically including:
[0124] 1.16 g of ammonium metatungstate and 0.78 g of nickel nitrate were dissolved in 24.85 g of deionized water to prepare a mixed impregnation solution. Separately, 12.78 g of tetrabutyl titanate and 8.28 g of pseudo-boehmite were prepared. The mixed impregnation solution and tetrabutyl titanate were simultaneously added dropwise to the pseudo-boehmite. The remaining procedures were the same as in Example 1 to produce a titanium-modified hydrorefining catalyst, designated TC-5.
[0125] The TC-5 catalyst contained 10 wt% tungsten oxide (main active metal component), 2 wt% nickel oxide (first auxiliary active metal component), and 30 wt% titanium oxide (second auxiliary active metal component) in the catalyst.
[0126] Example 6
[0127] This example refers to the preparation method of Example 1, and the difference from Example 1 is that the preparation conditions are changed, specifically including:
[0128] Aging conditions include: natural aging at 50°C for 20 h;
[0129] The calcination conditions include: calcination at 700° C. for 3 h; the remaining processes are the same as those in Example 1, and a titanium-modified hydrorefining catalyst is obtained, which is marked as TC-6.
[0130] The TC-6 catalyst contained 27 wt% of tungsten oxide (the main active metal component), 5 wt% of nickel oxide (the first auxiliary active metal component), and 10.2 wt% of titanium oxide (the second auxiliary active metal component) in the catalyst.
[0131] The composition of the catalyst products obtained in the above examples and comparative examples, the total acid content determined by pyridine infrared at 150°C, Ti 3+ The data of species peak area ratio, BET specific surface area, etc. are listed in Table 1 below.
[0132] Table 1
[0133]
[0134]
[0135] In Table 1, “——” indicates that it does not exist.
[0136] Reaction Test Example 1
[0137] This test example provides a test experiment of hydrogenating coked diesel using the catalysts prepared in the above examples and comparative examples.
[0138] The catalyst of the embodiment and the comparative example catalyst were compared respectively, and the reaction process was as follows: presulfurization was carried out before application to make the catalyst have better hydrogenation effect. Presulfurization was carried out using a 10mL high temperature and high pressure hydrogenation micro-reaction device. It was a wet in-situ presulfurization, i.e., wet presulfurization was used, and the catalyst was not unloaded after presulfurization, but directly continued to carry out hydrogenation reaction in the reactor. The presulfurized oil was a n-decane solution containing 5 wt% CS2, and the presulfurization temperature was 320°C, the pressure was 4MPa, and the liquid hourly mass space velocity was 1.5h -1 , the hydrogen-to-oil volume ratio is 300.
[0139] The hydrotreatment of this test example was carried out using a 10mL high temperature and high pressure hydrotreatment microreactor. The raw material used for evaluation was Daqing coking diesel, which has a specific gravity (d4 20 ) was 0.8274, the sulfur content was 1067ppm, and the total nitrogen content was 883ppm. The raw materials were pumped in by a plunger pump. The oil sample after reaction was cooled in the high separator and collected and analyzed in the low separator. The temperature of the hydrotreating was 300℃, the pressure was 4MPa, and the liquid hourly mass space velocity was 3.0h -1 The hydrogen-to-oil volume ratio was 500. The evaluation results of the hydrogenation catalyst are shown in Table 2.
[0140] The sulfur and nitrogen contents of the reactants and products were detected by ultraviolet fluorescence and chemiluminescence detection methods.
[0141] Desulfurization rate (mol%) = (raw material sulfur content - product sulfur content) / raw material sulfur content × 100%;
[0142] Denitrification rate (mol %) = (nitrogen content of raw material - nitrogen content of product) / nitrogen content of raw material × 100%.
[0143] Table 2
[0144]
[0145]
[0146] According to the data in Table 2 above, we can see that:
[0147] (1) Comparison of catalysts TC-1 and D-1, TC-2 and D-2, and TC-3 and D-3 shows that the titanium-modified hydrorefining catalysts TC-1 to TC-3 prepared in Examples 1 to 3 have higher desulfurization and denitrification rates in the coker diesel hydrogenation reaction;
[0148] (2) Comparison of Examples 1 to 4 with Comparative Example 4 shows that the composition of catalyst D-4 prepared in Comparative Example 4 is not within the range of "50 to 80 wt% of carrier, 10 to 40 wt% of main active metal component, 1 to 15 wt% of first auxiliary active metal component, and 1 to 30 wt% of second auxiliary active metal component". Compared with D-4, catalysts TC-1 to TC-4 prepared in Examples 1 to 4 have higher desulfurization and denitrification rates.
[0149] (3) Comparing Example 1 with Example 4, it can be seen that the preparation conditions of the catalyst preparation process of Example 4 are not within the scope of the present disclosure. Compared with the catalyst TC-4 prepared in Example 4, the catalyst TC-1 prepared in Example 1 has higher desulfurization rate and denitrification rate;
[0150] (4) Comparing Example 1 with Example 5, it can be seen that the component contents of the catalyst TC-1 prepared in Example 1 are within the preferred ranges disclosed herein (50-70 wt % of the carrier, 20-30 wt % of the main active metal component, 4-10 wt % of the first auxiliary active metal component, and 5-15 wt % of the second auxiliary active metal component). Compared with the catalyst TC-5 prepared in Example 5, the catalyst TC-1 prepared in Example 1 has higher desulfurization and denitrification rates.
[0151] (5) Comparing Example 1 with Example 6, it can be seen that the catalyst prepared in Example 1 according to the preferred reaction conditions of the present disclosure is used. Compared with the catalyst TC-6 prepared in Example 6, the catalyst TC-1 prepared in Example 1 has higher desulfurization rate and denitrification rate.
[0152] Reaction Test Example 2
[0153] This test example provides a test experiment of hydrogenating catalytic cracking diesel using the catalysts prepared in the above examples and comparative examples.
[0154] The catalyst of the embodiment and the comparative example catalyst were compared respectively, and the reaction process was as follows: presulfurization was carried out before application to make the catalyst have better hydrogenation effect. Presulfurization was carried out using a 10mL high temperature and high pressure hydrogenation micro-reaction device. It was a wet in-situ presulfurization, i.e., wet presulfurization was used, and the catalyst was not unloaded after presulfurization, but directly continued to carry out hydrogenation reaction in the reactor. The presulfurized oil was a n-decane solution containing 5 wt% CS2, and the presulfurization temperature was 320°C, the pressure was 4MPa, and the liquid hourly mass space velocity was 1.5h -1 , the hydrogen-to-oil volume ratio is 300.
[0155] The hydrotreatment of this test case was carried out using a 10mL high temperature and high pressure hydrotreatment microreactor. The raw material used for evaluation was Daqing catalytic cracking diesel, the specific gravity of which (d420 ) is 0.8894, the sulfur content is 1178ppm, and the total nitrogen content is 915ppm. The raw materials are pumped in by a plunger pump. The oil sample after reaction is cooled in the high separator and collected and analyzed in the low separator. The temperature of the hydrotreating is 300℃, the pressure is 4MPa, and the liquid hourly space velocity is 4.0h -1 The hydrogen-to-oil volume ratio was 600. The evaluation results of the catalyst after hydrotreatment are shown in Table 3.
[0156] The sulfur and nitrogen contents of the reactants and products were detected by ultraviolet fluorescence and chemiluminescence detection methods.
[0157] Desulfurization rate (mol%) = (raw material sulfur content - product sulfur content) / raw material sulfur content × 100%;
[0158] Denitrification rate (mol %) = (nitrogen content of raw material - nitrogen content of product) / nitrogen content of raw material × 100%.
[0159] Table 3
[0160]
[0161]
[0162] According to the data in Table 3 above, we can see that:
[0163] (1) Comparison of catalysts TC-1 and D-1, TC-2 and D-2, and TC-3 and D-3 shows that the titanium-modified hydrorefining catalysts TC-1 to TC-3 prepared in Examples 1 to 3 have higher desulfurization and denitrification rates in the catalytic cracking diesel hydrogenation reaction;
[0164] (2) Comparison of Examples 1 to 4 with Comparative Example 4 shows that the composition of catalyst D-4 prepared in Comparative Example 4 is not within the range of "50 to 80 wt% of a carrier, 10 to 40 wt% of a main active metal component, 1 to 15 wt% of a first auxiliary active metal component, and 1 to 30 wt% of a second auxiliary active metal component." Compared to D-4, catalysts TC-1 to TC-4 prepared in Examples 1 to 4 have higher desulfurization and denitrification rates in the catalytic cracking diesel hydrogenation reaction.
[0165] (3) Comparing Example 1 with Example 4, it can be seen that the preparation conditions of the catalyst preparation process of Example 4 are not within the scope of the present disclosure. Compared with the catalyst TC-4 prepared in Example 4, the catalyst TC-1 prepared in Example 1 has higher desulfurization rate and denitrification rate in the catalytic cracking diesel hydrogenation reaction;
[0166] (4) Comparing Example 1 with Example 5, it can be seen that the component contents of the catalyst TC-1 prepared in Example 1 are within the preferred range of the present disclosure. Compared with the catalyst TC-5 prepared in Example 5, the catalyst TC-1 prepared in Example 1 has a higher desulfurization rate and denitrification rate;
[0167] (5) Comparing Example 1 with Example 6, it can be seen that the catalyst prepared in Example 1 according to the preferred reaction conditions of the present disclosure is used. Compared with the catalyst TC-6 prepared in Example 6, the catalyst TC-1 prepared in Example 1 has higher desulfurization rate and denitrification rate.
[0168] The preferred embodiments of the present disclosure are described in detail above. However, the present disclosure is not limited to the specific details of the above embodiments. Within the technical concept of the present disclosure, various simple modifications can be made to the technical solutions of the present disclosure, and these simple modifications all fall within the scope of protection of the present disclosure.
[0169] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0170] In addition, the various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A titanium-modified hydrorefining catalyst, characterized in that: Based on the total weight of the titanium-modified hydrotreating catalyst, the titanium-modified hydrotreating catalyst includes 50 to 80 weight % of a carrier, 10 to 40 weight % of a main active metal component, 1 to 15 weight % of a first auxiliary active metal component and 1 to 30 weight % of a second auxiliary active metal component; the main active metal component is selected from one or more of the metal elements of Group VIB, the first auxiliary active metal component is selected from one or more of the metal elements of Group VIII, and the second auxiliary active metal component includes titanium; the carrier includes alumina.
2. The titanium-modified hydrotreating catalyst according to claim 1, characterized in that The main active metal component includes oxides of one or both metal elements selected from Mo and W; the first auxiliary active metal component includes oxides of one or both metal elements selected from Ni and Co; and the second auxiliary active metal component includes titanium oxide.
3. The titanium-modified hydrorefining catalyst according to claim 1, characterized in that The total acid content of the titanium modified hydrorefining catalyst measured by pyridine infrared at 150°C is 140-190 μmol / g. The acid center content is less than 10 μmol / g; Optionally, the BET specific surface area of the titanium-modified hydrorefining catalyst is 150 to 250 m 2 / g, the total pore volume is greater than 0.4cm 3 / g.
4. The titanium-modified hydrotreating catalyst according to claim 1, characterized in that The titanium-modified hydrotreating catalyst comprises Ti 3+ Species; Preferably, the Ti 2p 3 / 2 In the XPS spectrum of the orbital, the total titanium element peak area is used as the basis, and the Ti 3+ The peak area proportion of the species is 3 to 40%, preferably 8 to 20%.
5. A method for preparing a titanium-modified hydrorefining catalyst, characterized in that: The following steps are involved: S1, mixing a main active metal component precursor, a first auxiliary active metal component precursor, a second auxiliary active metal component precursor, water and an alumina precursor, and performing an aging treatment to obtain a catalyst intermediate; wherein the metal element of the main active metal component precursor is selected from one or more metal elements of Group VIB, the metal element of the first auxiliary active metal component precursor is selected from one or more metal elements of Group VIII, and the second auxiliary active metal component precursor includes a hydrolyzable titanium-containing compound; S2, mixing the catalyst intermediate with an auxiliary agent, and performing molding and calcining treatments.
6. The method according to claim 5, characterized in that The main active metal component precursor is selected from one or more of a molybdenum metal precursor and a tungsten metal precursor; preferably, the molybdenum metal precursor is selected from one or more of sodium molybdate, ammonium molybdate, molybdenum chloride and molybdic acid, preferably ammonium molybdate; the tungsten metal precursor is selected from one or more of ammonium metatungstate, phosphotungstic acid and silicotungstic acid, preferably ammonium metatungstate and / or phosphotungstic acid; The first auxiliary active metal component precursor is selected from one or more of a nickel metal precursor and a cobalt metal precursor; preferably, the nickel metal precursor is selected from one or more of nickel nitrate, basic nickel carbonate and nickel sulfate, preferably basic nickel carbonate and / or nickel nitrate; the cobalt metal precursor is selected from one or more of cobalt sulfate, cobalt carbonate, cobalt oxalate and cobalt nitrate, preferably cobalt nitrate and / or cobalt oxalate; The second auxiliary active metal component precursor is selected from one or more of titanium tetrachloride, methyl titanate, tetraethyl titanate, titanium n-propoxide, isopropyl titanate, tetrabutyl titanate, titanium tert-butoxide and titanium isooctoxide; preferably one or more of tetraethyl titanate, isopropyl titanate and tetrabutyl titanate; The aluminum oxide precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide and aluminum nitrate; preferably pseudo-boehmite.
7. The method according to claim 5, characterized in that In step S1, the aging treatment conditions include: natural aging at 0-50°C for 12-24h; Optionally, the method further comprises: drying the product obtained by the aging treatment at 80 to 160° C. for 4 to 12 hours.
8. The method according to claim 5, characterized in that In step S2, the calcination treatment conditions include: calcination at 300-700°C for 3-10 hours; the calcination atmosphere is one or more of air, nitrogen, oxygen, argon and water vapor; Optionally, before the calcination treatment, the product obtained by the molding treatment is dried at 80 to 160° C. for 4 to 12 hours.
9. The titanium-modified hydrorefining catalyst prepared according to the method according to any one of claims 5 to 8.
10. Use of the titanium-modified hydrotreating catalyst according to any one of claims 1 to 4 and claim 9 in a crude oil hydrotreating reaction.
11. The use according to claim 10, characterized in that: The following steps are involved: Under hydrogenation conditions, the crude oil is brought into contact with the titanium-modified hydrotreating catalyst to carry out a hydrotreating reaction; Optionally, the conditions of the hydrofining reaction include: reaction temperature of 260-380°C; hydrogen pressure of 4-10 MPa; hydrogen-oil volume ratio of 300-800:1; feed oil mass space velocity of 0.1-6h -1 ; Optionally, the feedstock oil is selected from gasoline and / or diesel fractions; Preferably, the method further comprises: performing a sulfiding treatment on the titanium modified hydrotreating catalyst before carrying out the hydrotreating reaction.
Citation Information
Patent Citations
Catalyst for hydrodesulfurization of hydrocarbons
CN1040610A
Fischer-Tropsch oil hydrofining catalyst, preparation method and application of Fischer-Tropsch oil hydrofining catalyst and Fischer-Tropsch oil hydrofining method
CN105772011A
Hydrogenation treatment catalyst and preparation method thereof
CN109772282A
Non-noble metal catalyst for hydrogen production through dehydrogenation of organic matters and preparation method and application thereof
CN111889093A
Carrier for organic compound dehydrogenation catalyst
CN111889095A